2005
DOI: 10.1089/cbr.2005.20.557
|View full text |Cite
|
Sign up to set email alerts
|

α-Particle Radioimmunotherapy of Disseminated Peritoneal Disease Using a 212Pb-Labeled Radioimmunoconjugate Targeting HER2

Abstract: These studies demonstrate the feasibility of targeted therapy for the treatment of disseminated peritoneal disease using (212)Pb-labeled Herceptin as an in vivo generator of (212)Bi. In vitro studies compare the potential of the bismuth radioisotopes, (213)Bi and (212)Bi, to that of (212)Pb. Overall, (212)Pb results in a higher therapeutic index than either bismuth radioisotope, requiring lower radioactivity (microCi) for effective cytotoxic response. A pilot radioimmunotherapy (RIT) experiment treating mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
141
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 27 publications
4
141
0
Order By: Relevance
“…tumors by 3-to 4-fold. 1,2 This therapeutic benefit can be potentiated by incorporating chemotherapeutics such as gemcitabine, paclitaxel or carboplatin into the treatment regimen. 3-5 213 Bismuth, a decay product of 225 Ac, has a T 1/2 of 45.7 min whereas 212 Pb is a 10.6 h half-life b ¡ -emitter that decays to 212 Bi, an a-emitter with a T 1/2 of 60.6 min.…”
Section: Introductionmentioning
confidence: 99%
“…tumors by 3-to 4-fold. 1,2 This therapeutic benefit can be potentiated by incorporating chemotherapeutics such as gemcitabine, paclitaxel or carboplatin into the treatment regimen. 3-5 213 Bismuth, a decay product of 225 Ac, has a T 1/2 of 45.7 min whereas 212 Pb is a 10.6 h half-life b ¡ -emitter that decays to 212 Bi, an a-emitter with a T 1/2 of 60.6 min.…”
Section: Introductionmentioning
confidence: 99%
“…According to Milenic and co-authors (32,33), this cell line possesses low but uniform expression of HER2 and may be a good model to demonstrate the sensitivity of Z HER2:342 in detection of lowlevel antigen expression. Female outbred Balb/c nu/nu mice were sc injected with one million LS174T cells in the hind leg 3 weeks before the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This laboratory recently showed the efficacy of two different a-emitting radionuclides in a peritoneal model for ovarian and pancreatic cancer using trastuzumab as the targeting moiety (3,4). HER2 is overexpressed in several epithelial tumors, including 35% to 45% of all pancreatic adenocarcinomas, 25% to 30% ovarian cancers, and 4% to 83% colorectal adenocarcinomas (5 -7).…”
mentioning
confidence: 99%
“…A specific dose response was observed when trastuzumab was radiolabeled with either 213 Bi or 212 Pb. Studies that exploited 212 Pb as an in vivo generator of 212 Bi clearly showed the feasibility of this isotope for targeted therapy treating disseminated peritoneal disease (4). Specifically, whereas HER2 was targeted using trastuzumab, the results therein also showed that at the protein doses used, the mAb itself provided no therapeutic benefit (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation